Biological nitrogen fixation by adesmia bicolor and A. Macrostachya, potential forage species for arid and semi-arid environments - Vileta, Dario German (2010)
In South American arid regions cattle feed lacks during winter. Adesmia bicolor and A. macrostachya are promising forage species because of their growth habit and adaptability to dry winters and N poor soils. Information about their biological nitrogen fixation (BNF) efficiencies is needed. The aim of this work is to determine their BNF efficiencies, nodule morpho-anatomy and spatio-temporal distribution, in symbiosis with rhizobia. In a greenhouse, both species were seeded and irrigated with nutritive solution: Without N; With N; and Inoculated seeds with nutritive solution without N. Nodules morpho-anatomy and spatio-temporal distribution; shoot-leaf, root, and nodule dry matter and N content were analyzed. The studied species showed a mean BNF efficiency of ~60%, which is a relatively high efficiency considering that alfalfa shows a 61% efficiency when grown in central Argentina. This attribute is desirable in wild species with forage potential in arid environments.